1999
DOI: 10.1242/jcs.112.23.4325
|View full text |Cite
|
Sign up to set email alerts
|

Molecular map of the desmosomal plaque

Abstract: Recent biochemical and molecular approaches have begun to establish the protein interactions that lead to desmosome assembly. To determine whether these associations occur in native desmosomes we have performed ultrastructural localisation of specific domains of the major desmosomal components and have used the results to construct a molecular map of the desmosomal plaque. Antibodies directed against the amino- and carboxy-terminal domains of desmoplakin, plakoglobin and plakophilin 1, and against the carboxy-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
19
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 193 publications
(24 citation statements)
references
References 73 publications
5
19
0
Order By: Relevance
“…Figure 1 depicts a representation of a desmosomal sub-unit, showing the localization of each protein as described in the literature, sizes and distances depicted are mostly based on the work of North et al. ( 20 ). To sensitively detect co-localization of the proteins, antibodies against epitopes in close proximity within the desmosomal intracellular region were selected ( Figure 1A ).…”
Section: Resultsmentioning
confidence: 99%
“…Figure 1 depicts a representation of a desmosomal sub-unit, showing the localization of each protein as described in the literature, sizes and distances depicted are mostly based on the work of North et al. ( 20 ). To sensitively detect co-localization of the proteins, antibodies against epitopes in close proximity within the desmosomal intracellular region were selected ( Figure 1A ).…”
Section: Resultsmentioning
confidence: 99%
“…S2). The cytoplasmic zone of the desmosome comprises an electron-dense outer plaque adjacent to the plasma membrane and a less electron-dense inner plaque that functions as an attachment zone for keratin intermediate filaments ( 10, 11 ). FIB-SEM imaging and 3D reconstructions revealed that peripheral ER tubules were in close contact with desmosomal plaques (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The keratin intermediate filament cytoskeleton anchors to the desmosome inner dense plaque, leading to the formation of a symmetrical adhesion structure ( 11 ). Since peripheral ER tubules were observed on either side of the desmosome, we investigated ER tubule localization relative to keratin filament bundles proximal and distal to desmosomal cell contacts.…”
Section: Resultsmentioning
confidence: 99%
“…Desmosomes are recognized in electron micrographs by spatial distribution of electron dense plaques of varying densities identified as outer dense plaques (ODP), inner dense plaques (IDP), and extracellular core (EC) (23,24) (Figure 1A). The components of these plaques were identified using immunoelectron microscopy (25).…”
Section: Desmosomesmentioning
confidence: 99%
“…The components of these plaques were identified using immunoelectron microscopy (25). A more precise localization of the terminal domains of the main desmosomal proteins has been achieved using the quantitative immunogold method (23). Accordingly, the intracellular core of Dsg and Dsc, Pg and Pkp, as well as the N terminus of Dp constitute the ODP, whereas the N domain of Dp forms the IDP (23) and anchors the desmosomal plaques to the intermediate filament cytoskeleton (26).…”
Section: Desmosomesmentioning
confidence: 99%